Impacts of the COVID-19 pandemic on the treatment of oncological patients: An ecological study (Research, Society and Development, 2022)
Cancer consists of a set of diseases whose defining characteristic is the disordered growth of cells. It is a major public health problem that, due to its complexity, has multiple forms of treatment, which consist of surgery, radiotherapy, chemotherapy and bone marrow transplantation. Due to the repercussion of the COVID-19 pandemic and its effects on the treatments of cancer patients, it was questioned whether the volume of cancer treatments had decreased during this period. The objective of this work was to analyze the number of cancer treatments in the pre-pandemic and pandemic periods of COVID-19 in different regions of Brazil. This is an ecological study, using data collected on the DATASUS-SIA-SUS website, with a time frame from 2018 to 2021. Data were analyzed using descriptive statistics, Durbin-Watson tests and Prais-Winsten regression. It was observed that the Southeast and Northeast regions presented the most accentuated reductions, being -36.92% and -36.57%, respectively. The capital Campo Grande showed an annual percentage variation of -42.15 with a confidence interval of 95% (-65.54; -18.76) and, therefore, a greater drop in the number of treatments. It was concluded that the COVID-19 pandemic interfered with the volume of cancer treatments, in such a way that Brazil showed a decreasing trend in the number of treatments in all Brazilian regions.